Epidemiology and Clinical Outcomes of Microscopic Colitis: Preliminary Results From the Loyola University Microscopic Colitis Registry (LUMiCoR) - Oruganti, Poornima; Awan, Rehmat; Ding, Xianzhong; Wesolowski, Michael; Abegunde, Ayokunle T. (Frontiers in Medicine, 2021)
Microscopic colitis (MC) is a common cause of chronic diarrhea with limited long-term data. We searched the pathology records at our institution from 2008 to 2018 to identify cases of MC. Total sample included patients with either a diagnosis of MC or incomplete MC (MCi).Chart review was performed and data were summarized for descriptive statistics. Logistic regression was used to estimate the unadjusted effects of predictors on MC. A total of 216 patients (88.32% white, 80.56% females, mean age 67.12 +/- 15.79) were studied; 50.00% had CC, 40.28% had LC and 9.72% had MCi. Majority (52.31%) were smokers and 21.84% of females were using some form of hormonal therapy. The odds of LC in reference to CC were significantly higher for those using tricyclic antidepressants (TCAs) (OR: 3.23, 95% C.I: 1.18- 8.80, p=0.02). The odds of smoking, statins, aspirin and beta-blocker use were decreased in MCi in reference to CC (all p< 0.05), 29(74.35%) patients with unresolved symptoms underwent repeat colonoscopies with biopsies. One case of MCi resolved, 8(72.73%) out of 11 cases of LC resolved, 2(18.18%) continued to be LC and 1(9.09%) transformed to CC, 8(47.06%) out of 17 cases of CC resolved, 8(47.06%) continued to be CC and 1(5.88%) transformed to LC. Majority of patients had CC. TCA use resulted in increased odds of LC in reference to CC. Biopsies from repeat colonoscopies in some patients revealed changes in the pathological diagnoses raising the question of interchangeability of MC (CC to LC and vice versa).